2012
DOI: 10.5923/j.am.20110101.03
|View full text |Cite
|
Sign up to set email alerts
|

Solution of Blasius Equation by Variational Iteration

Abstract: TheBlasius equation is a well known third-order nonlinear ordinary differential equation, which arises in certain boundary layer problems in the fluid dynamics. This paper presents a way of applying He"s variational iteration method to solve the Blasius equation. Approximate analytical solution is derived and compared to the results obtained from Adomian decomposition method. Comparisons show that the present method is accurate and the using of He"s method does accelerate the convergence of the power series. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Those comparisons point out that the VIM may be considered as an efficient alternative method for solving a wide range of physical nonlinear problems, especially those arising in the area of fluid dynamics. We point out how the VIM can also be applied to any heat transfer and flow problem leading to a coupled nonlinear system of ODEs, see for instance [5,14,16,17,23,31,35] without any claim to completeness. The major advantage of the VIM, unlike the common numerical methods, is of providing analytical approximation or an approximated solution without linearization, perturbation, closure approximation, or discretization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those comparisons point out that the VIM may be considered as an efficient alternative method for solving a wide range of physical nonlinear problems, especially those arising in the area of fluid dynamics. We point out how the VIM can also be applied to any heat transfer and flow problem leading to a coupled nonlinear system of ODEs, see for instance [5,14,16,17,23,31,35] without any claim to completeness. The major advantage of the VIM, unlike the common numerical methods, is of providing analytical approximation or an approximated solution without linearization, perturbation, closure approximation, or discretization.…”
Section: Discussionmentioning
confidence: 99%
“…Here we point out that just the first approximation y1 is capable to be an efficient approximation of the exact solution as is the case of the Blasius equation, see [17].…”
Section: Application Of Vimmentioning
confidence: 99%
“…, which is easily seen to have the theoretical solution u(x, t) = x 2 /2 + t. Using Eqn. (19) by assuming u 0 (x, t) = f(x) = x 2 /2, and other components can be obtained using the functional formula as:…”
Section: Examplementioning
confidence: 99%
“…Besides the aforementioned numerical methods, HVIM is an effective and convenient method for solving both weakly and strongly nonlinear equations, which was originally presented by He for solving differential equation systems [10][11][12][13]. The author has extensively applied HVIM for solving broad types of differential equation systems, such as heat equations, free vibration of Euler-Bernoulli beam, the nonlinear differential difference equations, Blasius equations, and [16][17][18][19]. From those works, it is found that both HVIM and ADM are efficient and powerful methods which can lead to correct solutions in closed form.…”
Section: Introductionmentioning
confidence: 99%
“…The accurate solution of Blasius equation has been obtained by numerical integration [1] and other numerical methods [3,4]. However, this fluid problem derived by the Blasius equation has been solved by various analytical methods [5,6].…”
Section: Fig 1: Velocity Boundary Layer Development On a Flat Plate [2]mentioning
confidence: 99%